A comparison of VLSM and VBM in a cohort of patients with post-stroke aphasia() - Geva, Sharon (Elsevier, 2012)
Studies attempting to map post-stroke cognitive or motor symptoms to lesion location have been available in the literature for over 150 years. In the last two decades, two computational techniques have been developed to identify the lesion sites associated with behavioural impairments. Voxel Based Morphometry (VBM) has now been used extensively for this purpose in many different patient populations. More recently, Voxel-based Lesion Symptom Mapping (VLSM) was developed specifically for the purpose of identifying lesion–symptom relationships in stroke patients, and has been used extensively to study, among others functions, language, motor abilities and attention. However, no studies have compared the results of these two techniques so far. In this study we compared VLSM and VBM in a cohort of 20 patients with chronic post-stroke aphasia. Comparison of the two techniques showed overlap in regions previously found to be relevant for the tasks used, suggesting that using both techniques and looking for overlaps between them can increase the reliability of the results obtained. However, overall VBM and VLSM provided only partially concordant results and the differences between the two techniques are discussed.